Functional and Radiological Outcome of Fixation in Terrible Triad Injury of Elbow - Suriyan Jeyasuresh; Palanikumar Madasamy; Suresh Kumar (Journal of Orthopedics and Joint Surgery)
Terrible triad injury (TTI) of the elbow is a complex elbow dislocation that consists of a head/neck of radius fracture, a fracture of the coronoid process, and posterior elbow dislocation/subluxation with or without ligament injury. Such injury makes the elbow unstable, demanding surgical fixation. The purpose of the study is to examine the functional and radiological outcomes of fixation in TTI of the elbow. Materials and methods: A total of 20 patients with terrible triad elbow (TTE) injuries were managed in the orthopedics department at Tirunelveli Medical College and Hospital. Preoperative X-rays, computed tomography (CT), and postoperative X-rays are used for the assessment of radiological outcomes. Patients were reviewed in the 6th week, 12th week, and thereafter every 3 months. The clinical outcome at 6 months was assessed using the Mayo Elbow Performance Score (MEPS). Results: The results were evaluated using the MEPS. Out of 20 patients, 16 patients had excellent scores, 3 had good scores, and 1 had a fair score at the 6-month follow-up. Conclusion: Due to the high risk of complications and the complexity of treatment required, TTI are challenging to manage. Through surgical fixation, patients with TTI can attain functional ratings ranging from good to exceptional with fewer problems if the intricacies of this injury and the underlying structures are properly understood.